Comparative Study on Attention Span among Undergraduate Students - Jiecel Aira Louise C. Jacildo; Joe Carlo C. Lopez; Maria Queenie Joy M. De Leon; Maria Ryza I. Almario; Jerald Q. Vergara; Kimberly Ann S. Cantilero (Future Science / FSH-PH Publications, 2025)
Students face challenges in maintaining attention span, potentially influenced by technology and multitasking habits demanded by the current school environment. Attention is the cognitive process that enables individuals to focus their senses on a specific stimulus, identify its characteristics, and extract meaningful information. This process is crucial in examining human behavior, as it impacts task performance, social interactions, and overall well-being. With the vast amount of information available on the internet, it has become increasingly challenging to navigate and generalize individual attention spans, especially in local contexts. Moreover, there are only a few studies regarding attention span among undergraduate students across year levels. This study employed a quantitative method, specifically a comparative design, to assess Filipino undergraduate students' capacity to sustain attention across different year levels at a private university in Pampanga, Philippines. The researchers employed a Kruskal-Wallis test to analyze data collected from 280 undergraduate students recruited through a quota-sampling technique. Findings revealed that there is no significant difference (p = 0.14) in the attention span of undergraduate students, leading to the conclusion that year level does not determine the attentional capacity of students. The findings emphasized the need for inclusive and adaptive teaching strategies that equally cater to all year levels. Furthermore, supporting students’ cognitive health across all stages of higher education, regardless of year level, promotes sustained academic performance and mental well-being.